Mechanical and hyperthermic properties of magnetic nanocomposites for biomedical applications. - Kan-Dapaah, K.; Rahbar, N.; Tahlil, A.; Crosson, D.; Yao, N.; Soboyejo, W. (Journal of the Mechanical Behavior of Biomedical Materials, 2015)
An understanding of the properties of multifunctional materials is important for the design of devices for biomedical applications. In this paper, a combination of experiments and models was used to study the mechanical and hyperthermic properties of magnetic nanoparticles (MNP)-filled PDMS composites for biomedical applications. These are studied as a function of the weight of MNP, γ-Fe2O3. The results showed the effects on mechanical behavior, and specific losses in a magnetic field. The measured Young's moduli are in good agreement with the moduli predicted from the Bergström-Boybce model. Specific losses calculated from magnetic measurements are used to predict the thermal dose under in-vivo conditions. The implications of the results were discussed for potential applications in biomedical devices.
Keywords: Biomedical devices; Magnetic nanocomposites; Magnetic nanoparticles; Polydimethylsiloxane